Pengembangan Multimedia Interaktif Dengan Pendekatan Kontruktivis Pada Mata Kuliah Teknik Digital - siti kholifah; Zaenal Mustofa; Paulus Hartanto (Universitas PGRI Semarang, 2019)
Abstract— This study aims to study the development process, the level of practicality, the level of validity, and the effectiveness of interactive multimedia with constructivist learning models to improve students' problem abilities. The research method used is R&D research using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation. The research subjects are STEKOM Semarang students. The results of the validation of media experts, material, media design, student responses and teacher responses are good criteria, namely for media experts 93.33%, 80.88% learning media design experts, 87.3% material experts, 87.5% used, and 87.5% lecturer responses, and 87.05% student responses.This media is practical to use. From the calculation of the N-Gain Test for the experimental and control class which has a different average NGain score of 0.419 and 0.132. One-party t-test was obtained and where, then Ho was rejected interactively with a constructivist learning model better than the problem solving abilities of students who using conventional learning.